Specific members of the predominant gut microbiota predict pouchitis following colectomy and IPAA in UC. Issue 1 (30th September 2015) - Machiels, Kathleen; Sabino, João; Vandermosten, Leen; Joossens, Marie; Arijs, Ingrid; de Bruyn, Magali; Eeckhaut, Venessa; Van Assche, Gert; Ferrante, Marc; Verhaegen, Jan; Van Steen, Kristel; Van Immerseel, Filip; et al.
Abstract : Objective: Pouchitis is the most common complication after colectomy with ileal pouch-anal anastomosis (IPAA) for UC and the risk is the highest within the 1st year after surgery. The pathogenesis is not completely understood but clinical response to antibiotics suggests a role for gut microbiota. We hypothesised that the risk for pouchitis can be predicted based on the faecal microbial composition before colectomy. Design: Faecal samples from 21 patients with UC undergoing IPAA were prospectively collected before colectomy and at predefined clinical visits at 1 month, 3 months, 6 months and 12 months after IPAA. The predominant microbiota was analysed using community profiling with denaturing gradient gel electrophoresis followed by quantitative real-time PCR validation. Results: Cluster analysis before colectomy distinguished patients with pouchitis from those with normal pouch during the 1st year of follow-up. In patients developing pouchitis, an increase of Ruminococcus gnavus (p<0.001), Bacteroides vulgatus (p=0.043), Clostridium perfringens (p=0.011) and a reduction of two Lachnospiraceae genera ( Blautia (p=0.04), Roseburia (p=0.008)) was observed. A score combining these five bacterial risk factors was calculated and presence of at least two risk factors showed a sensitivity and specificity of 100% and 63.6%, respectively. Conclusions: Presence of R. gnavus, B. vulgatus and C. perfringens and absence of Blautia and Roseburia in faecal samples of patients with UC before surgery is associated with a higher risk of pouchitis after IPAA. Our findings suggest new predictive and therapeutic strategies in patients undergoing colectomy with IPAA.